2019
DOI: 10.1186/s13046-018-1010-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Genistein inhibits stemness of SKOV3 cells induced by macrophages co-cultured with ovarian cancer stem-like cells through IL-8/STAT3 axis

Abstract: BackgroundRecent studies showed that macrophages co-cultured with ovarian cancer stem-like cells (OCSLCs) induced SKOV3 cell stemness via IL-8/STAT3 signaling. Genistein (GEN) demonstrates chemopreventive activity in inflammation-associated cancers. The present study aimed to examine whether and if GEN inhibits the stemness of SKOV3 and OVCA-3R cells induced by co-culture of THP-1 macrophages and SKOV3-derived OCSLCs.MethodsThe co-culture was treated with or without different concentrations (10, 20, and 40 μmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…5a). Since both IL-6 and IL-8 are reported to play a paramount role in macrophage polarization 21,22 , we herein investigated the contribution of IL-6, IL-8, or IL-6 and IL-8 together to the promotion of macrophage phenotype switching by GC-MSCs. First, increased phosphorylation of JAK2 and STAT3 in macrophages polarized by GC-MSCs was observed to be partly abrogated by either IL-6- or IL-8-specific neutralizing antibody treatment as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5a). Since both IL-6 and IL-8 are reported to play a paramount role in macrophage polarization 21,22 , we herein investigated the contribution of IL-6, IL-8, or IL-6 and IL-8 together to the promotion of macrophage phenotype switching by GC-MSCs. First, increased phosphorylation of JAK2 and STAT3 in macrophages polarized by GC-MSCs was observed to be partly abrogated by either IL-6- or IL-8-specific neutralizing antibody treatment as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Genistein exerted influence on the expression of inflammatory-related genes in breast cancer MCF-7 (high ERα/ERβ ratio), T47D (low ERα/ERβ ratio), and MDA-MB-231 (ERα-negative) cell lines [146]. Furthermore, genistein inhibited the increased M2 polarization of macrophages and stemness of ovarian cancer SKOV3 and OVCA-3R cell lines by the co-culture of macrophages with ovarian cancer stem-like cells through disrupting the interleukin (IL)-8/STAT3 signaling axis [147]. Isoflavone daidzein downregulated the pro-inflammatory NF-kB and JNK signaling pathways in adipocyte and macrophage co-cultures [148].…”
Section: Immunomodulatory and Anti-inflammatory Effects Of Flavonoidsmentioning
confidence: 99%
“…Specifically, there are some differences in M1 and M2 macrophages between murine and human 79. For instance, NO and Arg-1 were only expressed in murine macrophages and 12-O-tetradecanoylphorbol-13-acetate (PMA)-induced THP-1 macrophages, but not expressed in primary human monocyte-derived macrophages 914. Recent studies showed that tumor-associated macrophages (TAMs), predominantly M2 phenotype, are involved in tumor initiation and progression and promote neoplastic transformation by releasing factors during chronic inflammation 1,1518.…”
Section: Introductionmentioning
confidence: 99%